Bi‐Directional Spectro‐Polarimetry of Olivine Sand - Chris H. Lee; Charles M. Bachmann; Nayma Binte Nur; Rachel M. Golding (Earth and Space Science)
Abstract We characterized the bi‐directional spectro‐polarimetry of olivine sands of varying grain size distributions for a comprehensive set of measurement and illumination angles over a wavelength range of 350–2,500 nm. Our laboratory instrumentation included a hyperspectral goniometer, a broadband linear polarizer, and a tungsten‐halogen illumination source. Three distinct grain size distributions of olivine sand samples were used in our experiments. As a function of azimuth, we measured a significant degree of anisotropic scattering, that depends directly on polarization angles, resulting in a distribution that cannot be accurately described solely using phase angle. For media of uniform or similar composition, we observed robust separability of grain size distributions using spectro‐polarimetry. We compared Hapke's polarimetric model for semi‐infinite granular media with a new empirical polarimetric model that we developed. This empirical model more accurately replicates the scattering of unpolarized incident light as a function of all view azimuth, view zenith, and polarization angles for all incident zenith angles. Parameters of our empirical polarimetric model that determine the magnitude of polarization correlate linearly with the inverse diffuse reflectances of the olivine sand samples, exhibiting phenomenology that is most likely due to the Umov effect. Because of the linearity of the correlations, our results show that polarimetry can be used to retrieve medium parameters, such as grain size distributions. We provide our data online and freely available in a Zenodo/GitHub repository.